2021
DOI: 10.1007/s12032-021-01475-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of itraconazole on the clinical outcomes of patients with advanced non-small cell lung cancer receiving platinum-based chemotherapy: a randomized controlled study

Abstract: Itraconazole is an oral antifungal that has a been reported to have anticancer effect in non-small cell lung cancer (NSCLC) through inhibition of angiogenesis. The aim is to evaluate the effect of using itraconazole on the clinical outcome of metastatic NSCLC. This was a prospective randomized controlled open-label study conducted on 60 chemotherapy-naive metastatic NSCLC. Patients were simply randomized to either Control group who received platinum-based chemotherapy for a maximum of six cycles or Itraconazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Itraconazole was evaluated under randomized open-label placebo-controlled trial including chemo naïve advanced NSCLC patients treated with platinum-based chemo plus itraconazole regularly for 21 days or placebo. There was significant ORR, and PFS among groups but no difference in 1-year OS [31]. Anti-bacterial medications such as minocycline and doxycycline were found to be inhibit metalloproteinase and vascular endothelial growth factor (VEGF) reducing angiogenesis and degradation of extracellular matrix (ECM) [32, 33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Itraconazole was evaluated under randomized open-label placebo-controlled trial including chemo naïve advanced NSCLC patients treated with platinum-based chemo plus itraconazole regularly for 21 days or placebo. There was significant ORR, and PFS among groups but no difference in 1-year OS [31]. Anti-bacterial medications such as minocycline and doxycycline were found to be inhibit metalloproteinase and vascular endothelial growth factor (VEGF) reducing angiogenesis and degradation of extracellular matrix (ECM) [32, 33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Large studies have revealed that itraconazole in combination with other current agents made cancer patients benefit from oncotherapy in laboratory and clinical trials 4,49,50 . For example, combination chemotherapy with gemcitabine, nab‐paclitaxel, oxaliplatin and itraconazole (GnPO‐ITC) regimen showed promising efficacy with manageable toxicities for controlling disease progression and improving OS in pancreatic cancer patients 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 2 trial involving metastatic nonsquamous NSCLC, itraconazole combined with pemetrexed significantly prolonged the overall survival outcomes for patients by up to 32 months, compared to pemetrexed alone (8 months) (112). In a randomized controlled study investigating the effects of itraconazole on clinical outcomes in patients with advanced NSCLC receiving platinum-based chemotherapy, it was confirmed that itraconazole significantly improved 1-year PFS and overall response rates (ORR), but not 1year OS (113). The rationale for these two studies was based on anti-angiogenic effects of itraconazole.…”
Section: Recent Advances In Hh Inhibitorsmentioning
confidence: 95%